From Digital Inequality to Data Justice: The Phenomenon of Data Poverty in Statistical and Data Science Dimensions - OSAULENKOО. H.; MOTORYNR. М.; HOROBETSО. О. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article explores the phenomenon of data poverty as a novel dimension of digital inequality, encompassing technical, social, political, and ethical aspects. The relevance of this research stems from the recognition that data poverty extends beyond the mere technical issue of access to information; it reflects deeper systemic imbalances in the distribution of resources, digital policies, and participatory opportunities. Examining this phenomenon is critical for the development of equitable digital policy, particularly in countries like Ukraine, where the needs of the most vulnerable social groups must be addressed. The article proposes a conceptual model of interconnections between key dimensions of digital inequality-ranging from the digital divide as a foundational level of physical access to information and communication technologies, to the comprehensive category of data poverty, which integrates structural, analytical, and ethical dimensions of data use. This includes phenomena such as data divide, data marginalization, and data injustice, forming a systemic framework of digital unfairness. A comparative analysis of international indices relevant to the study of data poverty is also conducted. The study demonstrates that data poverty restricts the capacity of individuals, communities, and nations to act as active agents within the digital economy, public governance, and knowledge production. A typology of data poverty is proposed, comprising three levels of manifestation: individual level – where individuals or social groups remain excluded from digital analytics and statistical systems; institutional level – where public authorities lack sufficient, reliable data for informed decision-making; global / regional level – where countries serve merely as sources of raw data without having control over its processing, storage, and secondary use. The article also examines the geopolitics of data poverty, including digital colonialism and the asymmetry between data-rich and data-poor countries. Strategies for addressing data poverty are proposed, including the development of digital rights and data literacy, inclusive infrastructure, open data ecosystems, multi-sectoral partnerships, and ethically grounded data governance. The study argues that overcoming data poverty is not merely a technical task, but fundamentally a political and ethical challenge that requires rethinking data sovereignty, ensuring equitable access to data, and democratizing digital governance as the foundation for a just, inclusive, and sustainable digital future.